Prevalence and clinical relevance of 52-kDa and 60-kDa Ro/SS-A autoantibodies in Japanese patients with systemic sclerosis. Issue 11 (1st November 1997) - Fujimoto, M; Shimozuma, M; Yazawa, N; Kubo, M; Ihn, H; Sato, S; Tamaki, T; Kikuchi, K; Tamaki, K
Abstract : OBJECTIVE: To determine the prevalence of 52-Kda and 60-Kda Ro/SS-A autoantibodies in serum samples from Japanese patients with systemic sclerosis (SSc). METHODS: Serum samples from 263 Japanese patients with SSc were examined by double immunodiffusion and enzyme linked immunosorbent assay (ELISA). RESULTS: By double immunodiffusion, 29 serum samples from patients with SSc were found to possess anti-Ro/SS-A antibodies. By ELISA, 31 serum samples were positive for anti-Ro52 and/or anti-Ro60. Of 27 serum samples that were positive by both methods, 15 reacted with both Ro52 and Ro60, five with Ro52 alone, and seven with Ro60 alone. Eleven of 12 patients with both anti-Ro52 and anti-Ro60 and all five patients with anti-Ro52 alone had Sjögren's syndrome, while only one of six patients with anti-Ro60 alone had this disorder. CONCLUSIONS: Anti-Ro52 may be a serological marker for the presence of Sjögren's syndrome in anti-Ro/SS-A-positive patients with SSc.